2010
DOI: 10.1063/1.3309409
|View full text |Cite
|
Sign up to set email alerts
|

Shape effects in tapered metal rods during adiabatic nanofocusing of plasmons

Abstract: Optimized nonadiabatic nanofocusing of plasmons by tapered metal rods J. Appl. Phys. 104, 034311 (2008) We studied adiabatic nanofocusing of strongly localized surface plasmons in tapered metal rods with parabolic perturbations of the conical shape of the taper. Typical plasmon propagation parameters and local field enhancements are determined along the tapered rod, depending on the shape and plasmon frequency ͑wavelength͒. In particular, it is demonstrated that metal rods with tapered convex shape are more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
(107 reference statements)
1
15
0
Order By: Relevance
“…Recently, Vogel and Gramotnev theoretically investigated nanofocusing of SPPs in tapered metal nanorods with convex and concave perturbations of the conical shape under the adiabatic approximation conditions [325]. It is demonstrated that the nanorod with a tapered convex shape is more efficient in achieving larger local field enhancements at the tip than a nanorod with a concave shape.…”
Section: Nanorodsmentioning
confidence: 99%
“…Recently, Vogel and Gramotnev theoretically investigated nanofocusing of SPPs in tapered metal nanorods with convex and concave perturbations of the conical shape under the adiabatic approximation conditions [325]. It is demonstrated that the nanorod with a tapered convex shape is more efficient in achieving larger local field enhancements at the tip than a nanorod with a concave shape.…”
Section: Nanorodsmentioning
confidence: 99%
“…Another group of papers on the SPP on curved interfaces deals with numerical methods, see, for example, [16] and [17].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-gaps can be used for various trapping applications [2][3][4][5][6][7][8][9][10][11][12] as already demonstrated with cells 13 and conducting molecules 14 efficiently and without damage to biological material, due to their ability to produce strong light intensity gradients with low power. 15 Nano-gaps in metal nano-particles on dielectric substrates are promising for nano-focusing and nonlinear plasmonics, [16][17][18][19] as the localized surface plasmon resonance (LSPR) of particles is used to achieve a boost of sensitivity by field enhancement enabling single-molecule detection 20 , tweezing 21,22 , and can find applications in controlled polymerization on nano-scale [23][24][25][26] and micro-electrochemistry. 27 We developed bow-tie nano-antennas defined by electron-beam lithography (EBL) both with rounded shapes and fractal patterns designed to achieve broadband field enhancement from visible wavelength pushing to THz.…”
Section: Introductionmentioning
confidence: 99%